Between Certainty and Trust: Boundary-Work and the Construction of Archaeological Epistemic Authority. (December 2016) - Alonso González, Pablo
The discovery of a rock art site in 2008 by an amateur archaeologist spurred a wave of public interest in archaeology in Maragatería, Spain. As new discoveries took place, alternative archaeological discourses thrived facing the inaction of institutional and academic archaeologists. A long-term study of Maragatería carried out by the author serves to explore the construction of archaeological epistemic authority in a context where various social actors compete for dominance. Gieryn's notion of 'boundary-work' serves to analyse the different strategies employed by academic and institutional archaeologists, amateurs and pseudoarchaeologists to build epistemic authority. This article draws on Latour's affirmation that the legitimisation of scientific objectivity should rely on 'trust' rather than on 'certainty'. Ethnographic research showed that the more archaeologists attempted to legitimise their authority by reclaiming certainty, the more pseudoarchaeology proliferated. In contrast, the work of amateurs restrained the growth of pseudoarchaeology by creating networks of trust.